Cefotaxime incorporated bimetallic silver-selenium nanoparticles: promising antimicrobial synergism, antibiofilm activity, and bacterial membrane leakage reaction mechanism. Issue 41 (20th September 2022) - Elakraa, Abdelrahman A.; Salem, Salem S.; El-Sayyad, Gharieb S.; Attia, Mohamed S.
Abstract : In this research, we reported for the first time the simple incorporation of antibiotic cefotaxime (CFM) with Ag NPs, Se NPs, and bimetallic Ag–Se NPs by gamma rays; as a promising cost-effective, and eco-friendly method. Abstract : In this research, we reported for the first time the simple incorporation of antibiotic cefotaxime (CFM) with the synthesized Ag NPs, Se NPs, and bimetallic Ag–Se NPs by gamma rays, as a promising cost-effective, and eco-friendly method. The synthesized nanocomposites were characterized by UV-Vis. spectroscopy, XRD, EDX, HR-TEM, SEM/mapping, and EDX studies. The antimicrobial synergistic potential was investigated after CFM drug incorporation. Antibiofilm activity, growth curve assay, and effect of UV illumination were examined against some pathogenic microbes. The antibacterial reaction mechanism was evaluated by protein leakage assay and SEM imaging. HRTEM imaging confirmed the spherical shape and an average diameter of 10.95, 20.54, and 12.69 nm for Ag NPs, Se NPs, and Ag–Se NPs, respectively. Ag NPs-CFM, Se NPs-CFM, and Ag–Se NPs-CFM possessed antimicrobial activity against Staphylococcus aureus (40, 42, and 43 mm ZOI, respectively), Escherichia coli (33, 35, and 34 mm ZOI, respectively) and Candida albicans (25, 22, and 23 mm ZOI, respectively). CFM-incorporated Ag–Se NPs were able to inhibit biofilm formation of S. aureus (96.09%), E . coli (98.32%), and C. albicans (95.93%). Based on the promising results, the synthesized nanocomposites showed superior antimicrobial potential at low concentrations and continued-phase durability; they may find use in pharmaceutical, and biomedical applications.